Increased number of large non‐atretic follicles and co‐dominance effects account for high litter sizes in Bonga sheep - Tera, Asrat; Melesse, A.; Porcu, C.; Getachew, T.; Haile, Aynalem; Rouatbi, M.; Abate, Z.; Zeleke, M.; Rischkowsky, Barbara A.; Mwacharo, Joram M.; Rekik, Mourad (Wiley, 2020)
To understand the ovarian basis for prolificacy of Bonga sheep, a total of 31 ewes were selected based on litter size (LS) records and divided into two groups: High Prolificacy (HP) (n = 20) with LS ≥ 2 and Low Prolificacy (LP) (n = 11) with LS = 1. At a synchronized estrus, follicular dynamics were determined using transrectal ultrasonography. Plasma estradiol concentrations were also monitored. In total 27 ewes were observed in estrus being 9/11 LP (82%) and 18/20 HP (90%). On the day of estrus (day 0), the mean number of large follicles was higher (p < .05) in HP (1.78 ± 0.19) than in LP (1.0 ± 0.28) ewes. Prior to estrus, more (p < .05) medium follicles were visible for HP compared to LP ewes. Plasma estradiol concentrations were higher in HP compared to LP ewes (18.91 ± 0.41 vs. 14.51 ± 0.65 pg/ml; p < .05) and similarly was ovulation number (2.3 ± 0.15 vs. 1.28 ± 0. 14; p < .05). Higher ovulation rates and litter size in Bonga sheep are evidenced by the previous presence of more large follicles and the existence of co‐dominance effects as most likely medium follicles are selected to ovulate.